THERMAL DESIGN OF HTST MILK PATEURIZER USING HEAT PUMP - MAULANA SYARIEF (NIM : 13106033); Dosen Pembimbing: Dr. Ir. Abdurrachim Halim, DIKHA
Pasteurization methods, based on temperature and detention time, are divided into three types, LTLT, HTST and UHT. Based on the type of heat exchanger, the methods of pasteurization are divided into two major, continuous pasteurization using plate frame and batch pasteurization using agitated vessels. Batch pasteurization, including LTLT, is intended for small scale industry, while continuous pasteurization including HTST and UHT, are intended for large scale industry. LTLT pasteurization that is commonly used by small scale dairy farmers, has the disadvantage of the energy consumption for heating and cooling milk. The attempt to work on the disadvantage has found its way. The research conducted by Winfield (1996), the heat recovery from milk by water-cooled condenser mechanism is effective and provides a reliable source of heat for preheating water. In addition, Andersen (2000) reported that in some cases, high temperature absorption for heating recovery is more economically feasible then the absorption system for cooling purpose. Therefore, this study is conducted to carry out the application of heat pump in HTST pasteurizer design, with aim that energy required in pasteurization can be reduced. The design of the milk pasteurization that has 160 kg/hours capacity, gives the quite advantage because it can provides the energy needs for heating and cooling saved up to 63%.